Mechanism and principle of doping: realizing of silver incorporation in CdS thin film via doping concentration effect. Issue 46 (17th October 2022) - Najm, A. S; Aljuhani, Abdulwahab; Naeem, Hasanain Salah; Sopian, K.; Ismail, Raid A.; Holi, Araa Mebdir; Sabri, Laith S.; Abdullah AL-Zahrani, Asla; Rasheed, Rashed Taleb; Moria, Hazim
Abstract : A high-quality buffer layer serves as one of the most significant issues that influences the efficiency of solar cells. Abstract : A high-quality buffer layer serves as one of the most significant issues that influences the efficiency of solar cells. Doping in semiconductors is an important strategy that can be used to control the reaction growth. In this study, the influence of Ag doping on the morphological, optical and electrical properties of CdS thin films have been obtained. Herein, we propose the mechanism of CdS film formation with and without Ag ions, and we found that changes in the reaction of preparing CdS by the chemical bath deposition (CBD) method cause a shift in the geometric composition of the CdS film. XRD showed that the position of peaks in the doped films are displaced to wider angles, indicating a drop in the crystal lattice constant. The optical analysis confirmed direct transition with an optical energy gap between 2.10 and 2.43 eV. The morphological studies show conglomerates with inhomogeneously distributed spherical grains with an increase of the Ag ratio. The electrical data revealed that the annealed Ag-doped CdS with 5% Ag has the highest carrier concentration (3.28 × 10 15 cm −3 ) and the lowest resistivity (45.2 Ω cm). According to the results, the optimal Ag ratio was obtained at Ag 5%, which encourages the usage of CdS in this ratio as an efficient buffer layer on photovoltaic devices.